Avaliação da atividade antimicrobiana do fungo endofítico Paecilomyces lilacinus (THOM) Samson, frente a patógenos presentes em infecção endodôntica - Correia, Flávia Fontes Queiroz (2014)
Endodontics comprises the conservative and radical study of dental pulp, located within the root canals system. Once that oral microorganisms invade this system, the dental pulp enters in tissue necrosis, necessitating its removal, cleaning and shaping of the canals for posterior fillings, thereby reducing pathogens and allowing the body's defense to act, by preventing the progression and / or inducing regression of the disease. The common microorganisms in endodontic infections, which were used in this study are: Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus and Candida albicans. With the widespread use of antibiotics, several strains with resistance to current antibiotics has appeared, what justifies the search for new drugs of the genre. These are produced in small quantities by different sources, among them, plants and microorganisms. To minimize the extraction of flora, there is the alternative of using the endophytic microorganisms, since they may produce similar metabolites of those from its host. The endophytic fungus Paecilomyces lilacinus was isolated from the Amazonian plant Duguetia flagellaris (Anonnaceae), and it was cultured in broth: potato, dextrose and yeast extract for 16 days, at 28°C in a static mode. Then it was filtered, by separating the liquid portion (broth with secondary metabolites) from the solid one (mycelium). The broth was submitted to SPE extraction by using ethyl acetate / methanol 1:1 and methanol 100%, while the mycelium was extracted in 3 gradients. The first two gradients were equal of the SPE, and the last one was finished with 100% ethanol. The extracts were submitted to rotary evaporation, followed by lyophilization, and subsequently the antibiosis test by agar diffusion and microdilution was made. All the five extracts presented good results. For C. albicans and E. faecalis, the MID for the best extracts was (G2 and G4) with 62.5 mg / mL. For S. aureus and P. aeruginosa, it was (G4) less than 7.81 mg / mL. These results led to the fractionation of the extracts, to analyzes in CCD, to new tests of microdilution, bioautographic and decontamination of Gutta-Percha cones. All the obtained data corroborate the presence of at least six different molecules with these activities. The fractionation improved the MID for C. albicans with 15.62 mg / mL and to the other extracts presented no significant improvement. The bioautography with the best fractions and their extracts of origin showed good results for C. albicans, S. aureus and P. aeruginosa. The decontamination of Gutta-Percha cones was conducted with control of tetracycline, ampicillin, nystatin and sodium hypochlorite, presenting similar result to the controls. The extracts and fractions of P.lilacinus presented promising results of the inhibition of bacterial and fungal growth, and can be a source of compounds for use in dentistry or other health areas. Keys-words: endodontic, endophytic fungi, antibiosis.